Concentrations of Cadmium, Copper, and Zinc in Macrobrachium rosenbergii (Giant Freshwater Prawn) from Natural Environment - Farah Akmal, Idrus; Masania, Mohd Basri; Khairul Adha, A. Rahim; Chong, Melissa Dennis; Nur Syazwani, Abd Rahim (Springer New York LLC, 2018)
This study analyzed the levels of cadmium (Cd), copper (Cu), and zinc (Zn) by the flame atomic absorption spectrophotometer (FAAS), in the muscle tissues, exoskeletons, and gills from freshwater prawn (Macrobrachium rosenbergii) (n = 20) harvested from natural habitat in Kerang River, Malaysia on 25th November 2015. Significant increase of the metals level in muscle tissue and gill (r > 0.70, p < 0.05) were observed with increase in length except for Cu in gills. No relationship was found between metals level in exoskeleton and length. The concentrations of Cd, Cu and Zn were significantly higher (p < 0.05) in males (muscle tissues and exoskeleton) except for Cd in exoskeleton. In gills, only Cu was significantly higher (p < 0.05) in female than male. All samples contained metals below the permissible limit for human consumption (i.e., Cd < 2.00 mg/kg; Cu < 30.00 mg/kg; Zn < 150 mg/kg). Annual metals monitoring in prawn and environmental samples is recommended to evaluate changes of metals bioaccumulation and cycling in the system, which is useful for resources management. © 2018 Springer Science+Business Media, LLC, part of Springer Nature